1998
DOI: 10.1210/endo.139.11.6310
|View full text |Cite
|
Sign up to set email alerts
|

The New Antidiabetic Drug MCC-555 Acutely Sensitizes Insulin Signaling in Isolated Cardiomyocytes**This work was supported by the Ministerium für Wissenschaft und Forschung des Landes Nordrhein-Westfalen, the Bundesministerium für Gesundheit, EU COST Action B5, and a grant from Mitsubishi Chemical (Yokohama, Japan).

Abstract: Freshly isolated adult rat ventricular cardiomyocytes have been used to characterize the action profile of the new thiazolidinedione antidiabetic drug MCC-555. Preincubation of cells with the compound (100 microM for 30 min or 10 microM for 2 h) did not modify basal 3-O-methylglucose transport, but produced a marked sensitizing effect (2- to 3-fold increase in insulin action at 3 x 10(-11) M insulin) and a further enhancement of maximum insulin action (1.8-fold). MCC-555 did not modulate autophosphorylation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Exposure of insulin resistant cardiomyocytes obtained from obese Zucker rats to these TZDs also increased insulin sensitivity and restored glucose transport. This was associated with a reduction in the serine phosphorylation of IRS-1 (98). After 20 hours of incubation, there is a 3-fold increase in protein content of GLUT1, 1.5 fold increase in GLUT4 protein content and a 2-fold increase in GLUT4 abundance in plasma membranes that is associated with increased basal cardiac glucose uptake (99).…”
Section: Glucose Transporter Trafficking and Glucose Transport In Dia...mentioning
confidence: 95%
“…Exposure of insulin resistant cardiomyocytes obtained from obese Zucker rats to these TZDs also increased insulin sensitivity and restored glucose transport. This was associated with a reduction in the serine phosphorylation of IRS-1 (98). After 20 hours of incubation, there is a 3-fold increase in protein content of GLUT1, 1.5 fold increase in GLUT4 protein content and a 2-fold increase in GLUT4 abundance in plasma membranes that is associated with increased basal cardiac glucose uptake (99).…”
Section: Glucose Transporter Trafficking and Glucose Transport In Dia...mentioning
confidence: 95%
“…Several glucose-lowering agents, such as metformin or insulin, are the most prescribed drugs for managing blood glucose levels in SARS-CoV-2 infected patients. Interestingly, another anti-diabetic drug MCC-555 reported to sensitize insulin signalling, can aid in the proper management of blood glucose levels, and amend inflammatory responses during SARS-CoV-2 infections 60,61 . Bisdemethoxycurcumin, a naturally occurring curcumin analogue, and Icilin, an activator of Transient Receptor Potential Melastatin–8 (TRPM8), are reported to possess anti-inflammatory properties and may also attenuate systemic inflammation or lung injury 62,63 .…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that the pro-adipogenic and antiosteoblastogenic effects of Pparg are regulated by diverse downstream regulatory pathways that can be differentially modulated depending on the nature of the ligand. Ppar pan-agonist and dual-agonist drugs such as netoglitazone were thus developed to combine the triglyceride-lowering and HDL cholesterol-elevating effects of the Ppara (Ppara) agonists with the insulin sensitisation elicited by the Pparg agonists (Liu et al 1998, Upton et al 1998, Pickavance et al 1998, Chang et al 2007), while limiting negative effects on the skeleton (Lazarenko et al 2006). Unfortunately, to date, Pparg/Ppara dual agonist treatment is associated with unacceptable adverse effects that have delayed clinical application of these drugs (Chang et al 2007).…”
Section: Discussionmentioning
confidence: 99%